Stabilized blue emission from polymer-dielectric nanolayer nanocomposites - Park, JH; Lim, YT; Park, OO; Kim, JK; Yu, JW; Kim, YC (WILEY-V C H VERLAG GMBH, 2004)
Blue-light-emitting polymer (polyfluorene)/dielectric nanolayer nanocomposites were prepared by the solution intercalation method and employed in an electroluminescent (EL) device. Their photoluminescence (PL) and electroluminescence characteristics demonstrates that the interruption of interchain interaction in intercalated organic/inorganic hybrid systems reduces the low-energy emission that results from keto-defects. By reducing the probability that the excitons initially generated on the polyfluorenes will find keto-detects, both the color purity and the luminescence stability were improved. Furthermore, the dielectric nanolayers have an aspect ratio of about five hundred, and therefore act as efficient exciton blocking layers and barriers to oxygen diffusion, producing a dramatic increase in. the device stability. A nanocomposite device with a Li:Al alloy cathode gave a quantum efficiency of 1.0 %(ph/el), which corresponds to an approximate five times enhancement compared to the neat polymer device. The nanocomposite emitting layer is considered to have a pseudo-multiple quantum well structure.
Keywords: LIGHT-EMITTING-DIODES; GREEN EMISSION; PHOTOLUMINESCENCE; ELECTROLUMINESCENCE; POLARIZATION; COPOLYMERS